Microfungos associados à substratos vegetais submersos em ambiente lótico de um fragmento de Mata Atlântica, Bahia, Brasil - Barbosa, Flavia Rodrigues (2011)
Microfungi decomposing of submerged plant debris are important organisms in freshwater environments since they play a vital role in the flow of energy and nutrients. The knowledge of these fungi is still scarce, especially regarding their ecology, diversity and distribution patterns. To contribute to the knowledge of the biodiversity of ascomycetes and conidial fungi in fresh water in Brazil, a taxonomic study of this ecological group associated with submerged plant debris was conducted in a stream in Serra da Jibóia, Bahia, Brazil. Expeditions were conducted every three months from July 2007 to May 2009 to collect submerged bark, twig, leaf and petiole. The samples were washed in tap water and placed in moist chambers for three months. During this period, the samples were examined under a dissecting microscope and permanent slides were prepared with the reproductive structures of fungi. Taxonomic study of conidial fungi was conducted in the Mycology Laboratory of UEFS, while the taxonomic study of ascomycetes was carried out in the Mycology Laboratory of UIUC-USA. Permanent slides and dry material were deposited in the Herbarium HUEFS and cultures were deposited in “Coleção de Culturas de Microrganismos da Bahia” (CCMB). The first section presents a description of two new species and two new records of ascomycetes in the Annulatascaceae with illustrations and identification keys; the second section provides a description and illustrations of a new species of ascomycetes, Annulatascus apiculatus; in the third section, nine new records of ascomycetes are described and illustrated; in the fourth section, two new species of hyphomycetes are described and illustrated, and a list of 151 species of microfungi (ascomycetes, hyphomycetes and coelomycetes) is provided; in the fifth section the new species, Thozetella submersa is described and illustrated; the sixth section expands on the study of six rare species of hyphomycetes and lists 37 additional new records of hyphomycetes for western hemisphere, Neotropics, South America, Brazil and Bahia; in the seventh section new records of facultative freshwater aquatic fungi are provided with descriptions and illustrations.